2019
DOI: 10.3346/jkms.2019.34.e179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Outcome of Multi-Morbid Patients Cared for by Hospitalists: a Report of Integrated Medical Model in Korea

Abstract: Background The lack of medical personnel has led to the employment of hospitalists in Korean hospitals to provide high-quality medical care. However, whether hospitalists' care can improve patients' outcomes remains unclear. We aimed to analyze the outcome in patients cared for by hospitalists. Methods A retrospective review was conducted in 1,015 patients diagnosed with pneumonia or urinary tract infection from March 2017 to July 2018. After excluding 306 patients, 709… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Contrary to those studies, another report found no signi cant difference in mortality between patients treated by a hospitalist and those treated by a non-hospitalist [29][30][31][32][33][34]. Moreover, a recent Korean study found no difference in IHM between hospitalist and non-hospitalist care in the integrated medical model [34].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Contrary to those studies, another report found no signi cant difference in mortality between patients treated by a hospitalist and those treated by a non-hospitalist [29][30][31][32][33][34]. Moreover, a recent Korean study found no difference in IHM between hospitalist and non-hospitalist care in the integrated medical model [34].…”
Section: Discussionmentioning
confidence: 94%
“…Despite those con icting results, in our institute, AMU hospitalist care reduced the total LOS, compared to care from non-hospitalists. Recently, another study reported that hospitalist care within the integrated medical model of Korea showed a reduction in LOS, particularly in patients with multiple comorbidities [34]. According to that study, patients that received hospitalist care had shorter LOS, for several reasons.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations